2021
DOI: 10.2991/assehr.k.210615.034
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic Sequence at Gorga

Abstract: This research examines the process of making traditional Batak ornaments called gorga. The process will be analyzed mathematical concepts used in making gorga. Based on observations, one of the concepts used in making gorga is arithmetic sequence. This research is aimed at describing the modeling process carried out by engravers using local wisdom (emic) and relating it to academic mathematical modeling (etic). This research involved five gorga carvers in Tobasa and Samosir areas. Data was collected through di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, from the discovery of several mathematical aspects of Batak culture, such as geometric transformations in gorga (C. Ditasona, 2018), arithmetic sequences on gorga carvings (Candra Ditasona et al, 2021), 2d and 3d geometry concepts in traditional house (Hidayat et al, 2020), fractals on gorga motifs (Situngkir, 2012), the concept of flat geometry on ulos (Rahmadani & Reflina, 2023), as well as the integral concept of the taganing musical instrument can be utilized as a learning resource for local students. Thus mathematics is no longer seen as something abstract and foreign to students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, from the discovery of several mathematical aspects of Batak culture, such as geometric transformations in gorga (C. Ditasona, 2018), arithmetic sequences on gorga carvings (Candra Ditasona et al, 2021), 2d and 3d geometry concepts in traditional house (Hidayat et al, 2020), fractals on gorga motifs (Situngkir, 2012), the concept of flat geometry on ulos (Rahmadani & Reflina, 2023), as well as the integral concept of the taganing musical instrument can be utilized as a learning resource for local students. Thus mathematics is no longer seen as something abstract and foreign to students.…”
Section: Discussionmentioning
confidence: 99%
“…It takes special skills possessed by the sculptor to make gorga. Previous studies have shown that the concepts of transformation geometry and arithmetic sequences are used in making gorga (C. Ditasona, 2018;Candra Ditasona et al, 2021). Based on these findings, this study aims to analyze the patterns of symmetry in the various gorga motifs.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between mathematics and culture that underlies human activity is called ethnomathematics (Sari et al, 2021;Alghadari & Son, 2018;Ditasona, 2018;Ditasona, Turmudi, & Rosjanuardi, 2021). The idea of incorporating sociocultural elements into mathematics was initiated in 1977 by a Brazilian mathematician named Ubiratan D'Ambrosio.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ethnomathematics has been widely carried out in previous studies, one of which is on the ornaments of traditional houses in an area (Ditasona et al, 2022;Fitriza, 2018;Nurhikmah et al, 2019;Utami et al, 2021). These studies provide an understanding that in traditional house ornaments, there are mathematical ideas that are found and applied to traditional houses.…”
Section: Introductionmentioning
confidence: 99%